PENGARUH LEADER MEMBER EXCHANGE DAN KARAKTERISTIK PEKERJAAN TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) DENGAN MEDIASI KEPUASAN KERJA PEGAWAI (Studi pada Universitas Negeri Semarang) - Elsry Widaratri, 1342020036 (Jurnal Mahasiswa Pasca Sarjana, 2015)
The purpose of this study was to determine: the influence of Leader Member Exchange and characteristics of the work on Organizational Citizenship Behavior (OCB) mediated job satisfaction. The technique of testing data used in this study include validity, reliability, multiple regression analysis, model test, t test and mediation to test and prove the research hypothesis. Based on the results of the analysis and discussion shows that the Leader Member Exchange (LMX) positive and significant impact on job satisfaction pegawai.2) Characteristics Employment positive and significant effect on job satisfaction of employees 3). Leader Member Exchange (LMX) positive and significant impact on Organizational Citizenship Behavior (OCB) employees. 4). Job characteristics and significant positive effect on Organizational Citizenship Behavior (OCB) employees 5). Job satisfaction and significant positive effect on Organizational Citizenship Behavior- (OCB) employees. Keywords: Leader Member Exchange (LMX), job characteristics, OCB and job satisfaction